Early phase of COVID-19 epidemic in Albania. (March 2022) - Mersini, K.; Vasili, A.; Dervishi, M.; Kureta, E.; Robo, A.; Alla, L.; Daja, R.; Tomini, E.; Kota, M.; Simaku, A.; Hatibi, I.; Sulo, J.; et al.
Abstract : Purpose: The index case of COVID-19 was diagnosed on March 8th with symptoms onset identified on March 6th, with a travel history within Italy. During the first month the number of identified imported cases was 25. The first 291 laboratory-confirmed cases of the COVID -19 outbreak are used to characterize the epidemiological pattern and estimate the epidemiological parameters such as serial interval, basic and effective reproduction numbers and to evaluate the effectiveness of first timely disease spread containment measures. Methods & Materials: Epidemiological data were collected through case-based disease COVID -19 surveillance, outbreak investigation and contact tracing data for every confirmed case comprising information on demographics, travel history, date of symptom onset, clinical symptoms, laboratory results, hospitalization, and contacts details. Estimates of the reproduction number and serial interval were performed in R statistical software using R packages developed by the R Epidemics Consortium. Results: Public health authorities were able to identify and trace an average of 10 close contacts per for every positive case. The number of transmission events reported per infector ranges from 1 to 16, with 30% having two secondary cases per infector. The median value of every positive case was with 2 secondary infected cases (mean 3.3, standard deviation 3.2). Based on 43 pairs of primary infectors and secondary cases the mean serial interval was estimated 4.8 days (standard deviation 3.9). The basic reproduction number has been estimated at 2.19 (95% CI 1.6 to 2.8), while effective reproduction number showed a decreasing trend by the second week and reaching a plateau around the critical value during the first month. The social distance measures such as were implemented March 12 going to a total lockdown on March 15 with all travels suspended. Conclusion: Following the detection of the first COVID -19 case, Albania acted swiftly to implement immediate social distancing and lockdown measures. Such drastic measures had a huge effect on COVID-19 control in the beginning. However, the trend of effective reproduction numbers show a plateau for almost the last two weeks of the month with no signs of further decline.